A influência do market timing e do estágio do ciclo de vida na realização de ofertas públicas de ações - Costa, Vilma Sousa Ismael da (2013)
This study aimed to analyze whether the market timing and stage of life cycle influence the decision to perform a Public Seasoned Equity Offerings (SEO) in Brazilian companies traded. The analysis focused on whether the probability of a company conduct a SEO is positively related to the index MB (market-to-book), size and stock returns and profitability prior to completion of SEO, and negatively related to the stage lifecycle, profitability and stock return after completion of SEO. Initially we sought to examine the influence of the index market-tobook and returns and future steps in conducting a SEO. dditionally, we sought to examine the influence of firm age and number of years listed in BMFBOVESPA in making an SEO. And, in parallel, we attempted to verify the relationship between SEO and realization of the variables size and profitability. The population consisted of all n-financial companies, publicly traded, with shares traded on the Bolsa de Valores de São Paulo - BM & FBOVESPA, in the period from 2002 to 2010. The model follows the methodology used by H. Deangelo, L. Deangelo and Stulz (2010). Analyzing whether there is a relationship between the logistics company conduct a SEO and variable rate market-to-book, stage of life cycle, past returns and future profitability and size. About the variables we can conclude that there is a relationship between the attainment of SEO content and market-to-book, firm size and profitability after the completion of SEO. The relationships of the variables expected market-to-book and size, were confirmed as positive, however the variable profitability after completion of SEO obtained a negative relationship, thus diverging from the expected. Therefore, hypotheses 1 and 5 of the thesis, that the probability of performing SEO is positively related to the index market-to-book and size, can not be rejected. Descriptive statistics already pointed in this direction, about 81% of the operations were performed by SEO companies that presented index market-to-book more than 1, which indicates some sort of recovery, and the largest proportion, about 55% of the achievements were made by companies that were with index greater than 2.10 MB. Regarding the size, descriptive statistics already presented a preliminary support when showed that most of the offers, about 51% were held by companies that met the range of values of total assets (14 <log assets <16). Furthermore, there were no evidences that confirm the relationship of the stage of the life cycle, the stock return both the previous and subsequent to the achievement of SEO, and the operational performance before and the day of the year with the decision of SEO conduct a public seasoned equity offerings. Although the stage of the life cycle has not been found statistically significant evidence that shows that the vast majority of SEO s, about 57% were held by companies with up to 20 of the constitution, these data are confirmed when we used years BM & FBOVESPA's listing as a proxy for alternative stage of the life cycle, about 79% of SEO s were made by companies that have up to 15 years of listing. Regarding the stock performance of the ANOVA tests indicated an average return of shares a year before the superior achievement in comparison with stock returns one year after the completion of the SEO and the average stock returns in the subsequent year, the SEO companies that made and the companies that did not perform, are equal. The results point toward in favor of market timing theory as an explanation for the conduct of bids, i.e., companies realized the SEO when its shares were valued by the market, taking advantage of the time factor.